Um estudo sobre a democracia interna dos partidos políticos: os casos do PT e PSDB - Rodrigues, Marcus Leonardo Corrêa (2021)
This thesis investigated how intra-party democracy has unfolded within two of the largest Brazilian political parties: PT and PSDB. For such, based on a case study, we aimed at the identification to the potential synergies and/or tensions between intra-party democracy and the process of party institutionalization, the formal party organizational structures and the process of candidate selection in PT and PSDB parties. The case study was carried out based on quantitative data, bibliographical sources, documents and semistructured interviews with leaders and candidates that ran for the Chamber of Deputies by the state of São Paulo in the 2018 election. As a result, we identified the existence of contradictory trends related to the implementation of internal democracy within the political parties in question, which at times move towards an expansion of grassroots participation, while at other times advance towards the autonomy of the leaders in detriment to the grassroots party members.